Contemporary dilemmas in social work: The social work degree in England and its implications for practice - Higgins, Martyn (The Journal of Practice Teaching and Learning, 2018)
Abstract: The social work degree was established in 2002 to improve the status and competency of social workers. However, since then social work education continues to be subject to a series of significant changes. The aim of this study is to identify how the degree can illuminate the dilemmas of contemporary social work practice. A qualitative case study of a social work degree programme in England was undertaken after obtaining ethical approval. Data were collected at two different points in time by means of interviews and focus groups. Interviews were conducted with academics (10), practice educators (8) and academics involved in practice learning (2). Two focus groups were undertaken with service users (11) and three focus groups with students (17). A total of 48 participants were involved in the data collection. A thematic analysis approach using versus coding was adopted. The findings indicated that the social work degree contained inherent contradictions which were reflected in social work practice. The contribution of this study lies in the identification of dichotomies in social work education and practice. Any successful and lasting reform of social work education would have to adopt a critical framework able to address contemporary dilemmas. Keywords: social work degree; social work education; reform; dilemmas